Methods for Understanding and Analyzing NIBRS Data - Akiyama, Yoshio (Journal of quantitative criminology, 1999)
The National Incident-Based Reporting System (NIBRS) is an incident-basedcrime reporting program for local, state, and federal law enforcementagencies. Within each criminal incident, NIBRS captures information onoffenses, victims, offenders, property, and persons arrested, as well asinformation about the incident itself. The ability to link and analyze thisdetailed information is a significant improvement to the existing UniformCrime Reporting (UCR) summary reporting system. As one might expect,however, this increase in crime data significantly complicates the life ofthe data analyst, particularly when cross tabulating the NIBRS data. To dealwith the complexity of NIBRS data, one must understand its structure. Thisarticle provides an overview of the NIBRS structure and methods formaneuvering within it to present and interpret correctly cross tabulationsof the NIBRS data.